Innovation in the Design and Manufacture of Rice Fan Tools - Oknovia Susanti; Rizki Afriansyah; Fuadil Fajri Rozali; Yulinda; Hendri Yanda (Jurnal Penelitian Pendidikan IPA, 2025)
Rice is an agricultural product that is the staple food of the Indonesian people, the quality of rice yields is often unsatisfactory, because some of them have empty grains. So that farmers have to separate the filled rice grains from the empty ones manually, this process is considered less efficient. This process takes quite a long time. Therefore, a machine design is needed that can separate the filled grain from the empty grain. This research aims to design a rice fan machine, to make time efficient and to know the comparison between the manual process and the rice separator machine. This tool serves to separate good quality rice grains from grain (empty or imperfect rice grains), so that crop yields can be optimized. The working principle of this tool generally utilizes the difference in density between rice and grain with mechanisms such as air filtration (blower), vibration, or gravity.  In testing, the rice and grain fan showed a high level of accuracy in separation, with a capacity that can be adjusted based on the needs of farmers. This machine is able to separate rice 10kg/minute, which previously only 6kg/hour, there is an increase in the work efficiency of the tool in separating rice.